Biomorphic Transformations: A Leap Forward in Getting Nanostructured 3-D Bioceramics - Sprio, Simone; Ruffini, Andrea; Tampieri, Anna (Frontiers in Chemistry, 2021)
Obtaining 3-D inorganic devices with designed chemical composition, complex geometry, hierarchic structure and effective mechanical performance is a major scientific goal, still prevented by insurmountable technological limitations. With particular respect to the biomedical field, there is a lack in solutions ensuring the regeneration of long, load-bearing bone segments such as the ones of limbs, due to the still unmet goal of converging, in a unique device, bioactive chemical composition, multi-scale cell-conducive porosity and a hierarchically organized architecture capable of bearing and managing complex mechanical loads in an unique 3D implant. An emerging, but still very poorly explored approach in this respect, is given by biomorphic transformation processes, aimed at converting natural structures into functional 3D inorganic constructs with smart mechanical performance. Recent studies highlighted the use of heterogeneous gas-solid reactions as a valuable approach to obtain effective transformation of natural woods into hierarchically structured apatitic bone scaffolds. In this light, the present review illustrates critical aspects related to the application of such heterogeneous reactions when occurring in the 3D state, showing the relevance of a thorough kinetic control to achieve controlled phase transformations while maintaining the multi-scale architecture and the outstanding mechanical performance of the starting natural structure. These first results encourage the further investigation towards the biologic structures optimized by nature along the ages and then the development of biomorphic transformations as a radically new approach to enable a technological breakthrough in various research fields and opening to still unexplored industrial applications.